PENDAPATAN ASLI DAERAH (PAD): PAJAK DAERAH DAN RETRIBUSI DAERAH DI KABUPATEN BANGGAI LAUT - Syamsul, Syamsul; Irma, Irma (GOING CONCERN : JURNAL RISET AKUNTANSI, 2020)
This study aims to determine and analyze the level of effectiveness of revenue, growth, and contribution of the main components of local own income (PAD), namely local taxes and retribution. This research was conducted at the Department of Income Management of Finance and Assets (DPPKA) Banggai Laut County. Descriptive analysis shows the majority of the effectiveness of local taxes and retribution is very high and is included in the very effective criteria. Unfortunately, the growth of these types of local taxes and retribution is still considered unsuccessful. Meanwhile, the level of contribution of the types of local taxes and retribution is classified as very poor. In addition, the analysis also informs that several types of local taxes and retribution are included in the prime qualifications.